2003
DOI: 10.1067/mtc.2003.323
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxemia in coronary artery bypass surgery: A comparison of the off-pump technique and conventional cardiopulmonary bypass

Abstract: In conclusion, this study has shown that endotoxemia during coronary artery bypass surgery seems mainly to be associated with cardiopulmonary bypass procedure. The relatively lower endotoxin levels observed in off-pump surgery might contribute to improved postoperative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…It is possible that raised plasma LPS levels during CPB may trigger this CD163 shedding [17]. Such endotoxemia is thought to occur by gastrointestinal translocation and is less evident during OPCAB surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that raised plasma LPS levels during CPB may trigger this CD163 shedding [17]. Such endotoxemia is thought to occur by gastrointestinal translocation and is less evident during OPCAB surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increase in intestinal permeability and bacterial translocation (BT) has been demonstrated not only in animal models but also in patients during CPB [3,25,26] . Therefore, gastrointestinal integrity during the perioperative period is now recognized as an important factor for outcome of cardiac surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that even the usual use of CPB could induce endotoxemia. 14,15 Much stress, such as bacteremia and heart failure in the case of IE, induces mesenteric vasoconstriction, thus shunting blood toward more vital organs such as the heart and brain; the gut is one of the organs most susceptible to hypoperfusion. 16 Furthermore, cardioplegic arrest under the use of CPB should worsen any preexisting intestinal hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%